2016
DOI: 10.1093/humrep/dev337
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and fertility: women's accounts of healthcare

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 50 publications
4
65
1
Order By: Relevance
“…Similar essentialist ideas underlie observations that framing endometriosis as a fertility problem is more likely to result in health care intervention than when it is framed as symptom management. In one qualitative study, women described fertility as the entry point for discussion about endometriosis, despite having sought health care for symptoms over many years [12]. Existing evidence about best practice fertility-related care for women with endometriosis is sparse.…”
Section: A Contested Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Similar essentialist ideas underlie observations that framing endometriosis as a fertility problem is more likely to result in health care intervention than when it is framed as symptom management. In one qualitative study, women described fertility as the entry point for discussion about endometriosis, despite having sought health care for symptoms over many years [12]. Existing evidence about best practice fertility-related care for women with endometriosis is sparse.…”
Section: A Contested Diseasementioning
confidence: 99%
“…However, conflicting advice and treatment options, such as fertility testing (AMH and tubal patency) ovulation stimulation, oocyte retrieval and freezing, donor sperm, intrauterine insemination and IVF may be offered to women without acknowledgment of medical uncertainty, confirmation that a woman's fertility is actually compromised or that she desires or her social circumstances support her willingness to conceive. Participants reported satisfaction with care that involved sensitive inquiry and listening, and advice that acknowledges their sexuality and reproductive goals and that addresses their specific concerns with available evidence-based information [12]. Dyspareunia is a common and distressing symptom of endometriosis, and intimate relationships and sexuality are central concerns of couples experiencing infertility [13] argue that multi-disciplinary care should include sexology to address couples' psychosexual needs and promote wellbeing.…”
Section: A Contested Diseasementioning
confidence: 99%
“…This reduces ovarian reserve, and can end up in growing few oocytes and getting only a few embryos to transfer. 64,65 Ovarian Drilling Prior ART Recently, laparoscopic ovarian drilling (LOD) has been used widely by gynecologists as an alternative surgical method for ovulation induction using gonadotropins for polycystic ovary syndrome (PCOS) patients unresponsive to clomiphene, but there is a lack of consensus on effectiveness of this method. 66,67 Dale et al 68 conducted a study on the effectiveness of LOD on insulin resistance and pregnancy rate in patients with PCO.…”
mentioning
confidence: 99%
“…Another often-repeated "medical myth" is the assurance that undergoing hysterectomy will decrease or eliminate PPP [17,104]. Although the results of study IV showed a high satisfaction rate after hysterectomy (study IV), the pain mechanisms behind persistent pain and the characteristics of the disease do not preclude the pain from remaining even after hysterectomy.…”
Section: Endometriosis Healthcare Embraces Vital Dimensions Of Femalementioning
confidence: 98%
“…The experience of discussing fertility related to endometriosis has been reported previously. Many women have been advised to become pregnant in order to "cure" endometriosis [2,6,[102][103][104], even though pregnancy as a treatment for endometriosis is a "medical myth" that has not been empirically investigated, and is not recommended in clinical guidelines [4,45]. Such advice is problematic for several reasons: endometriosis is associated with both dyspareunia and subfertility.…”
Section: Endometriosis Healthcare Embraces Vital Dimensions Of Femalementioning
confidence: 99%